FRI0635 Description of videocapillaroscopy of the labial mucosa in comparison with nailfold videocapillaroscopy in scleroderma. (15th June 2017) - Beron, AM; duran, S Sapag; Laborde, H; Medina, G; Carrasco, M Garcia; Nasswetter, G; Dubinsky, D
Abstract : Background: Capillary bed of labial mucosa may be a potentially useful area for assessing abnormalities on the microcirculation. Videocapilaroscopy of the labial mucosa (LVC) in 12/13 scleroderma (SCL) patients showed capillaries disturbance such as great disorganization and anarchic orientation (1) . Objectives: To describe LVC features in SCL and compare them with healthy controls. (HC). To compare nailfold videocapillaroscopy (NVC) with LVC in HC and SCL patients. Methods: ≥16 years old patients with SCL (ACR-EULAR 2013) were included consecutively since June to July 2016. Smoking patients were excluded. For the evaluation of the LVC we performed a general displaying and then we studied following areas: a-central (1 cm from the frenulum), b-lateral right and left (both 2 cm from the frenulum) and c-labial border. For evaluation of the NVC, 200x images were obtained from 2nd to 4th fingers both hands and was classified according Cutolo in early, active, late patterns (2) . For assesment through LVC: photographs (200x) for each subject were taken. We define quantitative characteristics as means of: capillary diameter, length and density. The average of these parameters was obtained from the evaluation of capillaries included in 1 mm 2 of at least 2 continuous images. In addition, the visibility of the subpapillary venous plexus, architecture, dilatation of capillaries, presence of megacapillaries and avascular areas were qualitatively evaluated (photo 1). Each image was reviewed by two experienced observers. We conducted the same process describe above for each healthy control subject. Results: Twenty two patients were included (18 female, age 47±11 ys) with SCL (limited 17, diffuse 5); NVC pattern: early 8, active 11, late 3. Healthy subjects 12 (11 female, age: 34±10 years). Average capillary density: 17±4.13 (13–26) in SCL vs 21±3.65 (16–28) in HC (p 0.00). Average capillary diameter: 43±13.54 (17–83) SCL vs 19±1.67 μm (16–21) HC (p 0.02). Mean capillary length: 185±34 μm (125–248) SCL vs 237±42 μm (178–313) HC (p 0.00). In 22 SCL patients were observed dilated capillaries in 20 (90%), megacapillaries (≥70 μm) in 10 (45%) and 7 (32%) showed disturbed architecture with lost areas of the normal U-shape and changes in the parallelism of the main axis of the capillaries. About subpapillary venous plexus in SCL: 7 (32%) were prominent and only one had capillary hemorrhage. In contrast, none of the controls presented these alterations. (p 0.0). According to the 3 NVC patterns the following averages were observed in the LVC: Early Pattern (n: 8): diameter 36.93±10.84 μm; Long 191.21±47.58 μm; Density 18.12±5.33 μm. Active Pattern (n: 11): diameter 48.80±14.80 μm; Length 184.11±29.91 μm; Density 16.72±3.25 μm. Late Pattern (n: 3): diameter 36.27±10; Long 178.03±28.8 μm, density 19.33±4.16 μm. Conclusions: We found that LVC in SCL patients show significant microvascular changes with respect to HC. In addition, all NVC patterns described in SCL showed similar alterations in LVC. Therefore, LVC could be a complementary or alternative method to NVC since it is easily accessible, has good visibility and is not influenced by local mechanical or chemical stimuli that can affect the nail bed. References: W Grassi et al. Ann Rheum Dis 1993; 52 (8): 564–569. M. Cutolo et all. Rheumatology 2006; 45: 43–46. Disclosure of Interest: None declared